Enhancement of mesenchymal stem cell chondrogenesis with short-term low intensity pulsed electromagnetic fields - Parate, D.; Franco-Obregón, A.; Fröhlich, J.; Beyer, C.; Abbas, A.A.; Kamarul, Tunku; Hui, J.H.P.; Yang, Z. (Nature Publishing Group, 2017)
Pulse electromagnetic fields (PEMFs) have been shown to recruit calcium-signaling cascades common to chondrogenesis. Here we document the effects of specified PEMF parameters over mesenchymal stem cells (MSC) chondrogenic differentiation. MSCs undergoing chondrogenesis are preferentially responsive to an electromagnetic efficacy window defined by field amplitude, duration and frequency of exposure. Contrary to conventional practice of administering prolonged and repetitive exposures to PEMFs, optimal chondrogenic outcome is achieved in response to brief (10 minutes), low intensity (2 mT) exposure to 6 ms bursts of magnetic pulses, at 15 Hz, administered only once at the onset of chondrogenic induction. By contrast, repeated exposures diminished chondrogenic outcome and could be attributed to calcium entry after the initial induction. Transient receptor potential (TRP) channels appear to mediate these aspects of PEMF stimulation, serving as a conduit for extracellular calcium. Preventing calcium entry during the repeated PEMF exposure with the co-administration of EGTA or TRP channel antagonists precluded the inhibition of differentiation. This study highlights the intricacies of calcium homeostasis during early chondrogenesis and the constraints that are placed on PEMF-based therapeutic strategies aimed at promoting MSC chondrogenesis. The demonstrated efficacy of our optimized PEMF regimens has clear clinical implications for future regenerative strategies for cartilage.